Retrospective Analysis of Placental Invasion Anomalies in a University Hospital - Bıldırcın, Devran; Tosun, Miğraci; Malatyalıoğlu, Erdal; Yazıcı, Eren Ensari; Kefeli, Mehmet; Çetinkaya, Mehmet; Sakıncı, Mehmet; Çelik, Handan (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: Retrospective analysis of cases applying to the Gynecology and Obstetrics Clinic in Ondokuz Mayıs University Medicine School and diagnosed with placental invasion abnormalities, their common features and evaluation of test results STUDY DESIGN: Retrospective analyses and treatments were evaluated of cases applying to our clinic between February 2008 and February 2010 with placental invasion abnormalities and that diagnoses were ultrasonographically and pathologically finalized. RESULT: Four cases out of 6 were diagnosed preoperatively, and invasion of the bladder in one of these had been recognized preoperatively. All the cases had past cesarean section in their histories. Need for blood transfusion was less in cases diagnosed beforehand, and their hospitalization periods were shorter. Placenta previa was present in all the cases. Peripartum histerectomy was performed for all the six cases. Incidence of placental invasion abnormality was found as 1:294. This result may be cause of our university is a references origin in area. CONCLUSION: Maternal and fetal problems in cases of placenta invasion that are diagnosed previously and intervened after making the required preparations can be reduced.